The BOY with the BIGGEST HEAD in the WORLD - Peirce, Lincoln (London : HarperCollins Children's Books, 2025)
"Big-head Nate Wright truly believes he is destined for greatness! He's a table tennis champ, a genius comic book artist and the self-proclaimed king of his class. One school morning, Nate barely survives his dad's toxic porridge before rushing off to school, forgetting his lunch. He thinks he has a test and he hasn't studied for it!"--
Originally published: 2010.
Keywords: Big Nate -- (Fictitious character) -- Juvenile fiction; Families -- Juvenile fiction; Ambition -- Juvenile fiction; Schoolboys -- Juvenile fiction; School fiction; Humorous fiction